Improving neurodevelopmental outcomes in children with congenital heart disease: protocol for a randomised controlled trial of working memory training. Issue 2 (5th February 2019) - Calderon, Johanna; Bellinger, David C; Hartigan, Catherine; Lord, Alison; Stopp, Christian; Wypij, David; Newburger, Jane W
Abstract : Introduction: Executive function (EF) impairments are among the most prevalent neurodevelopmental morbidities in youth with congenital heart disease (CHD). To date, no studies have investigated the efficacy of cognitive interventions to improve EF outcomes in children with CHD. Methods and analysis: This is a single-centre, single-blinded, two-arm randomised controlled trial to test the efficacy of Cogmed Working Memory Training (Cogmed) versus standard of care in children with CHD after open-heart surgery in infancy. Participants will consist of 100 children with CHD aged 7–12 years who underwent open-heart surgery before the age of 12 months. Participants are randomly allocated to either an intervention group including training on the home-based Cogmed intervention for a duration of approximately 5 weeks or a control group who receive the standard of care. We will evaluate the efficacy of Cogmed at post-treatment and 3 months after completion of the intervention. Baseline, post-treatment and 3-month follow-up assessments will include specific measures of EF, cognitive and social functioning, and attention deficit hyperactivity disorder (ADHD) symptoms. The primary outcome of this study is the change in standardised mean score on the List Sorting Working Memory test from the National Institutes of Health Toolbox for the Assessment of Neurological and Behavioral Function. Secondary outcomes include measures of social skills, inhibitory control, cognitive flexibility and behavioural EF as well as ADHD symptoms as measured by the Behavior Rating Inventory of Executive Function, Second Edition, and the Conners Third Edition. The efficacy of the intervention will be evaluated by comparing within-subject differences (baseline to post-treatment, baseline to 3-month follow-up) between the two groups using an intention-to-treat analysis. Ethics and dissemination: This study has received Institutional Review Board (IRB) approval from Boston's Children's Hospital IRB (P00022440) and the Human Protection Agency from the US Department of Defense. Trial registration number: NCT03023644 ; Pre-results.